Reuse of anaerobically and aerobically pre-treated textile wastewater by UF and NF membranes - Debik, Eyup; Kaykioglu, Gul; Coban, Asli; Koyuncu, Ismail (ELSEVIER, 2010)
The aim of this study is to compare different pre-treatment techniques before the use of UF and NF membranes for textile industry effluents. Three different applications are discussed. First, raw textile wastewater effluent was applied to membranes (direct filtration of raw wastewater). After that, aerobically (full scale aerobic treatment plant (SBR) effluent that is present in the factory) and anaerobically (laboratory scale anaerobic treatment plant effluent) pre-treated effluents were compared with UF and NF membranes. UF and/or NF experiments were carried out at the laboratory scale and investigated at different operating pressures. The study showed that aerobic pre-treatment gave better performance prior to membrane filtration, and NF treatment with UF pre-treatment was the most suitable option for the effluents, as determined by different standards of permeate quality and quantity for different purposes in factories. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Textile wastewater; Aerobic treatment; Anaerobic treatment; Ultrafiltration; Nanofiltration; Reuse; INDUSTRY; REMOVAL; SLUDGE; Engineering; Water Resources